Assessment of Hospital Hyperglycemia and risk factors for diabetes in a university hospital (Research, Society and Development, 2022)
The objective was to evaluate the frequency of hospital hyperglycemia (HH) and risk factors for diabetes mellitus (DM) in non-critical patients hospitalized at the University Hospital of the Federal University of Sergipe (HU-UFS). This is a descriptive and cross-sectional study with convenience sampling. Data were collected by reviewing medical records and by interviewing research participants during the hospitalization period. The sample consisted of 140 patients, 77 (55%) women and 63 men (45%) with a mean age of 50.7 years and a mean BMI of 25 kg/m². Among the research participants, 40 (28.6%) had a previous diagnosis of DM and 85 (60.7%) patients did not have blood glucose levels compatible with HH. The frequency of HH was 15 (10.7%) with a relative risk significance value of p=0.01 with a 95% CI of 1.46 to 9.5. Among the risk factors for DM, history family was the one with the highest frequency 74.3%. Regarding comorbidities, 70 (50%) had SAH, 34 (24.2%) had DLP, while 14 (10%) had the 3 comorbidities (SAH, DM and DLP). It was identified that 20 patients did not present FGM at the time of admission, however, they had risk factors for DM. It is concluded that HH is frequent in our country and is associated with risk factors for DM. However, we evidence that its investigation is not carried out widely according to the recommendations of the current guidelines.